High-resolution two-dimensional imaging using MIMO sonar with limited physical size. (November 2021) - Liu, Xionghou; Wei, Tao; Sun, Chao; Yang, Yixin; Zhuo, Jie
Abstract: For an imaging sonar mounted onto a small sonar carrier (e.g., unmanned underwater vehicles), the angular resolution is strictly restricted by the limited physical size. To solve the problem, we propose a high-resolution imaging approach utilizing a multiple-input multiple-output (MIMO) sonar. The MIMO sonar is composed of two transmitting transducers and a receiving uniform linear array (ULA). The two transmitting transducers and the receiving ULA are located on two neighboring parallel straight lines, respectively. And the spacing between the two transmitting transducers is equal to the product of the hydrophone number and the inter-hydrophone spacing of the receiving ULA. Simultaneously, a pair of up- and down-chirp linear frequency modulation (LFM) pulses with the same frequency band (producing the same auto-correlation function for multibeam processing) and a large time-bandwidth product (ensuring low cross-correlation functions for range sidelobe suppression) are employed as transmitting waveforms. Based on the designed array layout and the transmitting waveforms, an improved hybrid beamformer combining the subarray processing, the phase shift and the shifted sideband beamformers together, is given, which ensures a fine imaging resolution and a low computation load. Via theoretical analysis, numerical simulations and a tank experiment, we show that the angular resolution of the proposed MIMO sonar imaging method doubles that of the traditional single-input multiple-output (SIMO) imaging method using the same array physical size and the same working frequency band.